Pemanfaatan Wadah Plastik Bekas untuk Bertanam Sayuran dalam Ketahanan Pangan Keluarga Masa Pandemi Covid19 Di Desa Padang Luas Kecamatan Tambang Kabupaten Kampar, Riau - Isda, Mayta Novaliza; Titrawani, Titrawani; Surjawati, Surjawati; Suhendra, Meyla; Fatonah, Siti (Universitas Nusantara PGRI Kediri, 2022)
Currently, the use of plastic containers is increasing which has an impact on landfilling because the material is difficult to decompose. One alternative effort to reduce plastic container waste is to use it as a vegetable growing medium. Vegetables that are grown can be consumed every day, which can increase the family's food, especially during the COVID-19 pandemic which has resulted in a weakening economy. Therefore, this training activity on the utilization of used plastic waste containers was carried out in Padang Luas Village, Tambang Sub District, District Kampar, Riau. This activity aims to provide knowledge, insight and stimulate creativity in processing plastic waste to the community in utilizing used plastic containers to grow vegetables. Methods of training activities include material presentation, demonstration of making plant pots from used plastic, and making plant pots with the community. The training activities have proceeded as planned. The results of the questionnaire after the training activities showed that most of the people gave a positive response and would apply the knowledge they gained from the training. Overall, participant answer really liked (54%) and liked (46%) the use of plant pots from used plastic containers. This training activity can be the beginning of the implementation of the use of used plastic waste to be more useful.